Association Between Sleep Problems and Symptoms of Attention Deficit Hyperactivity Disorder in Adolescence: Results From a Large Population-Based Study. Issue 5 (2nd September 2016) - Hysing, Mari; Lundervold, Astri J.; Posserud, Maj-Britt; Sivertsen, Børge
Abstract : Sleep problems and symptoms of ADHD are common in adolescence, but detailed epidemiological assessment of their association is lacking. Using data from a recent population-based study, 9, 846 adolescents aged 16 to 19 provided detailed information on sleep and symptoms of ADHD. Results confirmed a large overlap between self-reported symptoms of ADHD and all sleep variables studied. Symptoms of ADHD were linked to shorter sleep duration, longer sleep latency, and nocturnal wake time, as well as larger sleep deficiency. ADHD symptoms also increased the odds of insomnia and delayed sleep phase syndrome. The associations were only partially explained by confounders (mainly depression). The findings suggest that sleep problems should be included as a treatment target in efforts to reduce symptoms of ADHD in adolescence.